2006
DOI: 10.1038/sj.jp.7211602
|View full text |Cite
|
Sign up to set email alerts
|

Prenatal rectal perforation: an unsuspected cause of isolated ascites

Abstract: In fetal intestinal perforation, inflammation leads to production of ascites. Small bowel is usually involved by perforation with the distal ileum the most frequent site. We report the first case of prenatal perforation of the intraperitoneal part of the rectum, which presented as severe ascites at a 37 weeks' gestation antenatal ultrasonography. As none of the reported causes of intestinal perforation were identified in our case, its etiology remained idiopathic.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 13 publications
0
6
0
Order By: Relevance
“…Meconium may also track in a supralevator direction to enter the abdominal cavity as observed in 3 of our cases. A neonate with intraperitoneal rectal perforation [9] presenting as neonatal ascites has also been described. This variation seems to occur less frequently than FERP but reassuringly demonstrates the complete anatomical spectrum of antenatal rectal perforation.…”
Section: Discussionmentioning
confidence: 99%
“…Meconium may also track in a supralevator direction to enter the abdominal cavity as observed in 3 of our cases. A neonate with intraperitoneal rectal perforation [9] presenting as neonatal ascites has also been described. This variation seems to occur less frequently than FERP but reassuringly demonstrates the complete anatomical spectrum of antenatal rectal perforation.…”
Section: Discussionmentioning
confidence: 99%
“…5 In prenatal intestinal perforation, distal ileum is the most frequently involved segment. 6 The extrusion of meconium can appear as a solitary mass inside foetal ascites or as disseminated echogenic masses. Establishing the etiology of intestinal perforation can be challenging.…”
Section: Discussionmentioning
confidence: 99%
“…In the majority of cases, it is caused by intestinal perforation secondary to bowel obstruction or meconium ileus [9]. Small bowel, particularly distal ileum, is the most commonly affected part and prenatal perforation of the rectum is extremely rare [10]. Less common causes of meconium peritonitis include volvulus, imperforate anus and meconium plugs.…”
Section: Discussionmentioning
confidence: 99%
“…They reported a good outcome when identified and managed appropriately. Casaccia et al [10] reported the first case of intraperitoneal fetal rectal perforation that presented as isolated ascites without any associated mass in the perineum. The authors described the fetal ascitic fluid as hyperechoic suggestive of possible fetal intestinal perforation.…”
Section: Discussionmentioning
confidence: 99%